PELATIHAN PUBLIC SPEAKING UNTUK MENUNJANG KEMAMPUAN PRESENTASI SISWA DI DESA SINDANGJAYA - Salma, Zalfa Naufali Nadita; Asmara Dwi Aksa, Yudha; Marginingsih, Ria (Universitas Islam 45 Bekasi, 2023)
Ability in public speaking is an important part of every activity, especially activities in the academic environment. In reality, there are still few school students who have public speaking skills. Departing from this, the author conducts Public Speaking Training which will be held at MTs Fatahillah Sindangjaya Village. The methods used in this training are material delivery, discussion and simulation. This study aims to present sources of related topics in an effort to support presentation skills for students located in Sindangjaya Village. Data in this study was collected using interviews, web scraping and documentation. The results of this study show that students can understand how to speak and present well and correctly. It is hoped that this activity can increase the literacy of students' abilities in public speaking which can be used as a key to the advancement of a civilization in a country.